2023
DOI: 10.1007/s12306-022-00771-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome and quality of life following resection of the proximal humerus performed for musculoskeletal tumors and reconstruction done by four different methods

Abstract: Introduction The proximal humerus is a frequent site for both primary and secondary bone tumors. Several options are currently available to reconstruct the resected humerus, but there is no consensus regarding optimal reconstruction. The aim of this retrospective study was to compare the functional outcome, complications and patient compliance following four different types of reconstructive techniques. Material and methods The authors performed 90 proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…This is especially important if the deltoid can be preserved; however, reconstructions can still be performed using a reverse APC when margins necessitate removal of a portion of or the entire deltoid and/or axillary nerve 50,51 . Additional series (Tables III and V) have also shown that rAPC offers the greatest improvements in functional outcomes with a reduction in complications that are typically associated with reconstruction 26,48,75,77 . Reverse APC reconstructions are not without their own complications.…”
Section: Allograft Prosthetic Compositementioning
confidence: 94%
“…This is especially important if the deltoid can be preserved; however, reconstructions can still be performed using a reverse APC when margins necessitate removal of a portion of or the entire deltoid and/or axillary nerve 50,51 . Additional series (Tables III and V) have also shown that rAPC offers the greatest improvements in functional outcomes with a reduction in complications that are typically associated with reconstruction 26,48,75,77 . Reverse APC reconstructions are not without their own complications.…”
Section: Allograft Prosthetic Compositementioning
confidence: 94%
“…Antal, et al (2023) 7 showed that six developed complications (24%) in the autologous fibula transplantation group. Four complications (40%) occurred in the group of 10 patients who received a massive osteoarticular allograft.…”
Section: Complicationsmentioning
confidence: 99%
“…Functional Outcomes: Musculoskeletal Tumor Society (MSTS) score Antal, et al (2023) 7 showed that the best scores were found in the reverse shoulder prosthesis-bone allograft composite group, the score was 84%. Whereas MSTS score in the autologous fibula transplantation group was MSTS score was 70%.…”
Section: Complicationsmentioning
confidence: 99%